Reconstructing Indonesian Family Law through Local Wisdom-Mediated Dispute Resolution: Advancing Restorative Justice in Household Conflicts - Sofia Gussevi; Dulnasir Dulnasir; Khoir Affandi (Jurnal Iman dan Spiritualitas, 2026)
Domestic conflict resolution in Indonesia relies heavily on formal litigation, often leading to divorce and fractured social bonds—contradicting Pancasila's emphasis on deliberation, family harmony, and societal peace. This study analyzes local wisdom's role in developing restorative justice-oriented mediation models and reconstructing family law to better align with Indonesia's socio-cultural context. Employing a juridical-sociological approach, it qualitatively examines Supreme Court Regulation No. 1/2016 on court mediation and regional customary practices. Findings reveal local wisdom-based mediation's potential to foster reconciliation, restore relationships, and achieve moral equilibrium. Thus, family law reconstruction is essential: legally recognize customary mediation, integrate traditional leaders into pretrial processes, and enact culturally adaptive regulations—advancing progressive law rooted in national values.